2020
DOI: 10.1111/jbi.13957
|View full text |Cite
|
Sign up to set email alerts
|

Climate as a major driver of avian diversity in riparian Amazonian habitats along an environmental gradient

Abstract: Aim: To investigate the influence of bioclimatic, productivity and topographic variables on avian diversity patterns in riparian habitats along a savanna/humid forest environmental gradient. We investigate how this gradient affects patterns of taxonomic and phylogenetic alpha and beta diversities, and whether the changes observed along the river are the result of taxonomic (and phylogenetic) replacement or nestednessresultant dissimilarities. We also explore a potential ecological mechanism to account for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
4
10
0
Order By: Relevance
“…Our results were consistent with those of many previous studies [18,32,33]. For example, dominated taxonomic replacement and functional nestedness were also found for waterbird communities across anthropogenic subsidence wetlands in the North China Plain, suggesting that the taxonomic turnover may be mainly driven by functionally redundant species [33].…”
Section: Higher Taxonomic and Phylogenetic Turnover But Lower Functio...supporting
confidence: 92%
See 2 more Smart Citations
“…Our results were consistent with those of many previous studies [18,32,33]. For example, dominated taxonomic replacement and functional nestedness were also found for waterbird communities across anthropogenic subsidence wetlands in the North China Plain, suggesting that the taxonomic turnover may be mainly driven by functionally redundant species [33].…”
Section: Higher Taxonomic and Phylogenetic Turnover But Lower Functio...supporting
confidence: 92%
“…For example, dominated taxonomic replacement and functional nestedness were also found for waterbird communities across anthropogenic subsidence wetlands in the North China Plain, suggesting that the taxonomic turnover may be mainly driven by functionally redundant species [33]. In addition, an avian study in riparian Amazonian habitats also found dominated taxonomic and phylogenetic replacements, highlighting the crucial role of transition zones and ecotones for avian taxonomic and phylogenetic diversity conservation [32].…”
Section: Higher Taxonomic and Phylogenetic Turnover But Lower Functio...mentioning
confidence: 89%
See 1 more Smart Citation
“…Climatic factors such as precipitation and temperature are related to the variation in beta diversity patterns (Naka et al, 2020;Wayman et al, 2021). We found that precipitation was an important factor in explaining the variation in beta diversity patterns in the W Himalaya.…”
Section: Role Of Environmental Filteringmentioning
confidence: 68%
“…Biotic factors (intra‐ and interspecific interactions between species) may also be regulated by abiotic factors such as climate. Climate may alter species abundance (Naka et al., 2020) or modify the power of biotic interactions (Early & Keith, 2019; Romero et al., 2018). For example, climate might affect the ability of vertebrates to capture their prey (Woodroffe et al., 2017), or the strength of predation by arthropods (Romero et al., 2018), which potentially could alter the outcomes of interspecific interactions and cause spatial or temporal mismatches between interacting species (Early & Keith, 2019; HilleRisLambers et al., 2012).…”
Section: Introductionmentioning
confidence: 99%